Prinsip moralitas merek dalam undang-undang nomor 20 tahun 2016 tentang Merek dan Indikasi Geografis - Sulthon Miladiyanto; Ariyanti Ariyanti (Jurnal Cakrawala Hukum, 2020)
The responsibility of the state cannot maintain the morality of the people, one ofwhich is by providing signs in making trademarks for goods and services. Legalresearch with a philosophical approach to get the meaning of Brand must not conflictwith the prevailing morality in society. A moral brand is a brand that limitssociety which is universal regarding the pros and cons of an act of both ratio andtracendetal involving the goal.How to cite item: Miladiyanto, S., Ariyanti, A.(2020). Perinsip moralitas merek dalam undang-undang nomor 20 tahun 2016 tentangMerek dan Indikasi Geografis. Jurnal Cakrawala Hukum, 11(3).,241-249. doi:10.26905/idjch.v11i2.5022.